THE EFFECT OF TREE STRATEGY ON STUDENTS' ACHIEVEMENT IN WRITING ANALYTICAL EXPOSITION TEXT - GABBY MAUREEN PRICILIA; Habib Rahmansyah (Jurnal Education and Development, 2018)
One of the curriculum’s expectations at the eleventh grade students of SMA Negeri 1 Sayurmatinggi is students are able to write exposition text. But in fact, students’ achievement is unsatisfied so that the writer decides to conduct a research in that field. The aims of this research are : 1) to know the extent of students’ achievement in writing analytical exposition text at the eleventh grade students of SMA Negeri 1 Sayurmatinggi before taught by TREE strategy, 2) to know the extent of students’ achievement in writing analytical exposition text at the eleventh grade students of SMA Negeri 1 Sayurmatinggi after taught by TREE strategy, 3) whether there is a significant effect of students’ achievement in writing analytical exposition text taught by TREE strategy at the eleventh grade students of SMA Negeri 1 Sayurmatinggi. The population of this research is all of the eleventh grade students of SMA Negeri 1 Sayurmatinggi and the sample is 31 students which are taken by cluster sampling technique. The instrument to collect data used is writing test. The result of analyzed data shows that the score of ttest is 7.8 while the score of ttable is 1.67. it shows that ttest is higher than ttable. It means that there is a significant effect of students’ achievement in writing analytical exposition text at the eleventh grade students of SMA Negeri 1 Sayurmatinggi taught by TREE strategy.